[End of innocence ; Off the balance beam ; Life after Ms. Saigon [videorecording] /executive producer, Cheche Lazaro]. - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Looks into the case of twelve-year-old girl claiming she was raped by her playmates, aged nine to thirteen, gymnasts claiming politics exists in gymnastics officials; and interview with Monique Wilson who played Kim in Ms. Saigon.
End of innocence (13 min.) -- Off the balance (14 min.) -- Life after Ms. Saigon (21 min.)
VHS.
Keywords: Wilson, Monique -- Interviews; Rape -- Philippines; Child molesting -- Philippines; Gymnasts -- Philippines; Sports -- Corrupt practices